Experimental Study on Behaviour of Steel composite Blocks Using Epc - J, Arunprasad; M, Lakshmi Priya; M, Kokila (International Research Journal of Multidisciplinary Technovation, 2019)
Concrete is the most important engineering material and the addition of some other material may changes the properties of concrete. This research is carried out to produce a low cost and eco-friendly concrete steel blocks. Studies have been carried out to investigate the possibility of utilization a broad range of material of partial replacement of coarse aggregate. Here the partial replacement of coarse aggregate by expanded polystyrene in the percentage of 25%, 30%, 35%. The tests were carried out on standard cube of 150x150x150mm for 7, 14, 28 days to determine the optimum percentage replacement. The steel blocks are made in dovetail shape and EPC is poured in it. The strength of steel composite blocks are then studied. The aim of the research is to know the behavior of steel composite blocks after addition of EPS and find its application.